MULTIPLE ROLE OF WOMAN’S PERFORMANCE IN INDONESIA: STUDY ON NURSING MEDICAL PERSONNEL - Maramis, Mauna T. B.; Saerang, David P. E.; Adolfina; Lengkong, Victor P. K. (International Journal of Research -GRANTHAALAYAH, 2020)
Motivation/Background: In Indonesia, labor force participation is dominated by men while woman's participation is only half. This study was conducted to examine the dual role conflict of women in health workers in Indonesia. The research was conducted on female nurses at the Provincial Hospital of North Sulawesi Province: Prof. Dr. Kandou Manado Method: The total number of questionnaires distributed was 200 questionnaires, with the response rate was 60% or 120 respondents. The majority of respondents, are young workers aged 27-36 years, the last education was diploma 3 in nursing, having 3-5 children. To test the hypothesis it was found that a positive and significant relationship between work-family conflict to work stress and organizational commitment to woman's performance in multiple roles was accepted. Another hypothesis relationship tested is rejected. Results: The results of the study are described in the discussion above which finds various influences and relationships between variables of this study. The dual role of women on performance at work is influenced by various variables. Conclusions: These results have an impact on hospital organization as well as on future research.